Efficacy and Safety of Sodium Tanshinone IIA Sulfonate Injection on Hypertensive Nephropathy: A Systematic Review and Meta-Analysis - Xu, Junyao; Zhang, Chenghua; Shi, Xiaoqing; Li, Jie; Liu, Ming; Jiang, Weimin; Fang, Zhuyuan (Frontiers in Pharmacology, 2019)
Background: Sodium Tanshinone ⅡA Sulfonate Injection (STS), the extractive of traditional Chinese medicine Danshen, is supposed to be a supplementary treatment in hypertensive nephropathy. Objectives: To evaluate the efficacy and safety of STS in treatment of hypertensive nephropathy. Methods: We systematically searched China National Knowledge Infrastructure (CNKI), Chinese Scientific Journals Database (VIP), Wan-fang database, Chinese Biomedicine Database (CBM), PubMed, EMBASE, Web of Science, and Cochrane Library from their inception to November, 2018. All studies were screened by two reviewers according to the inclusion and exclusion criteria independently. The Cochrane Collaboration's risk tool was used to assess the methodological quality of the included studies. Reviewer Manger 5.3 was employed for statistics analysis. Results: Sixteen trials involving 1696 patients were included. The meta-analysis results indicated a combination of STS and ARBs was more effective than ARBs monotherapy in modulating hypertensive nephropathy, as represented by improved eGFR [MD = 6.87, 95% CI (4.47, 9.28), P < 0.00001] and reduced 24-hour urinary protein [MD = -0.23, 95% CI (-0.27, -0.19), P < 0.00001], SCr [MD = -21.74, 95% CI (-24.11, -19.38), P < 0.00001], cystatin-C [MD = -0.16, 95% CI (-0.24, -0.07), P = 0.0003], urinary IgG [MD = -0.85, 95% CI (-1.11, -0.59), P < 0.00001] and urinary transferrin [MD = -0.61, 95% CI (-1.04, -0.17), P = 0.007]. In addition, the combination therapy had better control in SBP [MD = -6.53, 95% CI (-8.19, -4.87), P < 0.00001] and DBP [MD = -4.14, 95% CI (-5.69, -2.59), P < 0.00001]. Only 3 trials reported adverse events, and no adverse drug reactions were observed. Conclusions: STS combined with ARBs had a stronger effect on improving renal function in patients with primary hypertensive nephropathy than ARBs monotherapy. The combination therapy also provided auxiliary hypotensive effects. Further large-scale, multicenter, and rigorously designed RCTs should be conducted to confirm our findings.